Neumotórax y su incidencia en la insuficiencia respiratoria en pacientes críticos en la unidad de cuidados intensivos en el hospital del IESS del cantón Babahoyo los ríos primer semestre 2018 - Alcivar Bonoso, Hector Alfredo (2018)
In the present work of study refers to the respiratory insufficiency presented by a pneumothorax in which can be caused by a trauma at the level of the rib cage or by an underlying disease these traumas affect the health of citizens. The number of possible causes of respiratory failure is very large, but we must consider the patient's condition and determine the length of time he has been hospitalized: an asthmatic crisis, even if only temporary, can be a cause for serious concern. The following activities were carried out: socialization of the topic with the relatives, direct observation, data collection for its tabulation and interpretation. The application of the action plan, identification of signs and symptoms of respiratory failure and the importance of Respiratory Therapy to avoid complications in the disease. The methodology used was the descriptive, analytical-explanatory because it is intended to analyze the various risk factors that lead to respiratory insufficiency generated by a pneumothorax and the line of research used was health management and disease prevention.